Hidden hunger: A global problem with local solutions - Ulimwengu, John M.; Domgho, Léa Magne; Collins, Julia; Badiane, Ousmane (AKADEMIYA2063, 2023)
Micronutrient deficiencies are widespread in many low- and middle-income countries, but tend to be most severe in children and in pregnant women, who have higher micronutrient requirements. Micronutrient deficiencies stem from inadequate intake or absorption of vitamins and minerals which are required for normal functioning of the body; they cause specific conditions and also affect overall health, growth and development, resistance to disease, cognitive function, and energy and productivity. Common micronutrient deficiencies include those for iron, vitamin A, iodine, folate, and zinc. The most widespread micronutrient deficiency at the global level, iron deficiency causes anemia and contributes to maternal deaths and impaired child development. Vitamin A deficiency is the primary cause of preventable childhood blindness and a major contributor to child sickness and deaths from other diseases. Iodine deficiency in pregnant women can lead to lifelong neurological and cognitive issues in children. Folate deficiency during pregnancy also affects fetal development and can cause low birth weight and neural tube defects. Zinc deficiency impairs overall growth and development and is believed to be a leading contributor to overall disease burden in developing countries.